The Multimedia and Technology of Teachers for Chinese Language Teaching - Thanapongpichat, Apisara (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2023)
At the present, multimedia and technology are important to all language teaching, including the Chinese language. This is because there are various applications for Chinese vocabulary teaching. These applications help to facilitate learners to learn the meaning and to put words into sentences in conversation. Therefore, multimedia and technology are important factors in educational management in the modern world. It also changes traditional teaching and motivates learners based on information technology in Digital Era. This academic article focuses on the importance and concept of using multimedia and technology in teaching Chinese, such as practicing language skills, transferring language knowledge, and understanding teachers and learners, which will be the basis for further language learning. The previous studies provided both the theoretical and conceptual framework and international documents related to multimedia and information technology for Chinese teaching. The research findings found that integrating multimedia and technology blended teaching and learning management can increase learning opportunities and teaching and learning efficiency, including developing the quality of education in Chinese. In addition, the sharp gravel and a variety of multimedia and technology are also helping teachers' teaching and learning, enhancing the quality of Chinese language teaching.